Assessing Prevalence of Osteoporosis and Identifying Risk Factors in Interstitial Lung Disease Patients - Madeha Shahid, Saadia Uzair, Abdul Salam, Ibrahim Ali Khan, Ankash Kumar, Faheem Ahmed Solangi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic lungdiseases are severe diseases which have a wide prevalence of osteoporosis in them. These chronic lung diseases include cystic fibrosis, bronchial asthma, bronchiectasis, and chronic obstructive pulmonary disease. However, there is only limited data available that define its risk factors and its prevalence in patients that have Interstitial Lung Disease (ILD). Objective: The purpose of this research is to study patients with ILD and determine the risk factors and prevalence of osteoporosis in ILD patients. Study Design: A cross-sectional study Place and Duration: This study was conducted at Gulab Devi Chest Hospital Lahore from December 2021 to December 2022 Methodology: A total of 80 patients participated in this research. This research is a cross-sectional analysis of all of those patients who had ILD. Every patient that was already admitted to the hospital was a part of this study. The clinical data and demographics of each participant were noted down. In order to measure the density of the bone mineral, an absorptiometry scan (x-ray), which was of dual-energy, of the femoral neck of the patient was performed. To identify osteoporosis, T-scores were considered, as we were following the guidelines of the World Health Organization. The risk factors were identified by conducting multivariate as well as univariate logistic regression analysis. Results: The majority of the sample size were females, representing 67.5 percent of the participants (n=54). The average age was 55.8 years. There were 32 patients in whom osteoporosis was identified. Univariate analysis showed certain factors that were positively related to osteoporosis. These factors include the time period of symptoms, female gender, and a low hemoglobin level. Multivariate analysis showed the hemoglobin level and the time period of symptoms as independent risk factors. Conclusion: In patients that are diagnosed with Interstitial Lung Disease, osteoporosis is a common problem. The existence of osteoporosis in these patients can be determined by low hemoglobin levels and the longer time period of the symptoms. Keywords: Interstitial Lung Disease. Osteoporosis, chronic lung disease, adults